Kinerja Keuangan Usaha Mikro dan Kecil - Winbaktianur; Liesma Maywarni Siregar (LPPM Universitas Pelita Bangsa, 2020)
SMEs is one of the basic forms of business stance developed from an individual or a group of people. In practice there has been a lot of support given to this business category even though the products or services is still small competing with medium and large businesses. Planning and control needs to be done which is the goal the main thing is to achieve the goal. Planning is made for facilitate the assessment or evaluation of business activities. Performance appraisal is important to see to what extent the business that is carried out has reached the goal, financial performance how much profit is obtained in a period. The purpose of this research is to discuss the importance of conducting a performance appraisal micro and small scale entrepreneurship. The method of this paper is library research. In discussion, it will describe what assessment is performance, performance appraisal factors and indicators as well as terminated with the benefit of doing a financial performance appraisal. Keywords: Micro and Small Enterprises, performance appraisal, entrepreneurship